If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = -3h + -10 Reorder the terms: -3 = -10 + -3h Solving -3 = -10 + -3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3h' to each side of the equation. -3 + 3h = -10 + -3h + 3h Combine like terms: -3h + 3h = 0 -3 + 3h = -10 + 0 -3 + 3h = -10 Add '3' to each side of the equation. -3 + 3 + 3h = -10 + 3 Combine like terms: -3 + 3 = 0 0 + 3h = -10 + 3 3h = -10 + 3 Combine like terms: -10 + 3 = -7 3h = -7 Divide each side by '3'. h = -2.333333333 Simplifying h = -2.333333333
| a/13=-29 | | 4(q-2)=16q | | 60+r=360 | | -5(1+6v)=27+2v | | 4x+-4=4x+52 | | 10z+1=7 | | (y^3+8)-5(2+y)=184 | | 2x=2(x+4) | | 44-2x=9x | | 10(2y+2)-y=-2(8y-8) | | 4/5(5x-30)=56 | | h/15=8/25 | | 5(4x-7)-5=5(x-3)+65 | | x^2+16x+145=0 | | (1/3)(6x+9)=x-5 | | 5n-(-2)=2 | | 12=n/-3+10 | | 6+7x+2-3x=0 | | v-9=19 | | G=D+Drt | | 79.5=0.1T+72.9 | | -2/9n+(-6)=2 | | X-(4/100)x=23.04 | | 16+3/4x=28 | | 12/48=6/20 | | 48=3d+8 | | 0.06x+1.8=2-2.251 | | 77n^2+28n=0 | | 5n+-2=27 | | -5n+2=27 | | 29=5+3h | | -2u-10=-7u+20 |